The future of the European Union : the trade unions' demands and expectations for the intergovernmental Conference 1996. - European Trade Union Institute (ETUI) (Brussels : ETUI, 1996)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: vakbonden; Europese Unie (EU).